Does cryotherapy improve skin circulation compared with compression and elevation in preventing venous leg ulcers?. Issue 4 (10th August 2016) - Kelechi, Teresa J; Mueller, Martina; Madisetti, Mohan; Prentice, Margie A; Dooley, Mary J
Abstract: This trial compared skin blood flow, temperature and incidence of venous leg ulcers in patients with chronic venous disease using compression wraps and elevation pillows. Patients with CEAP C4 skin damage and C5 history of ulcers were randomly assigned to a cryotherapy intervention ( n = 138) or placebo cuff control ( n = 138) applied to the lower legs over 9 months. The time the ulcers healed prior to enrollment in the study for the cryotherapy group ranged from 1 to 2218 days ( n = 8, median = 32 days); for the control group, the range was 24 to 489 days ( n = 6, median = 390 days). There were no statistically significant blood flow changes measured in perfusion units with a laser Doppler flowmetre within or between the groups; mean difference between the groups was 0·62, P = 0·619. No differences were noted in skin temperature measured with an infrared thermometer within and between the groups; mean difference between the groups was −0·17°C, P = 0·540. Cryotherapy did not improve skin blood flow or temperature and did not show efficacy in preventing ulcers. However, at least 30% of intervention and 50% of control participants were anticipated to develop an ulcer during the study; only ∼7% occurred. These findings suggest that strict adherence to standard of care decreases the incidence of leg ulcers and remains a best practice for leg ulcer prevention.